Common infections, mental health problems and healthcare use in people with inflammatory bowel disease: a cohort study protocol. Issue 2 (17th September 2020) - Irving, Peter; Barrett, Kevin; Tang, Daniel; Nijher, Monica; de Lusignan, Simon
Abstract : Introduction: People with inflammatory bowel disease (IBD) are at increased risk of pneumonia and herpes zoster, yet other common infection types have not been explored. Anxiety and depression are more prevalent in IBD; however, the impact of these conditions on primary care healthcare use in IBD is not known. Methods and analysis: We will perform two retrospective studies using a large English population-based primary care cohort to compare the following outcomes in people with IBD and matched controls: incident infections (Study 1) and prevalent mental health problems and healthcare use, overall and in those with and without mental health problems (Study 2). All adults registered with general practices contributing to Royal College of General Practitioners Research and Surveillance Centre database between 1 January 2014 and 1 January 2019 are eligible. Infection outcomes comprise the incidence of common infections (upper respiratory tract infections, pneumonia, acute bronchitis, influenza and influenza-like illnesses, skin infections, herpes simplex and herpes zoster infections, genital infections, urinary tract infections and gastrointestinal infections) and any viral infection. Mental health and healthcare use outcomes are: prevalence of depressive episodes; anxiety episodes; recurrent depression; rates of primary care and emergency secondary care visits; primary-care issued sick notes (reflecting time off work). Analyses will be adjusted for sociodemographic factors recorded in the primary care record. Discussion: These studies will quantify the infection risk in IBD, the excess burden of anxiety and depression in a population-based IBD cohort, and the impact of mental health conditions on healthcare use and time off work. Greater understanding and awareness of infection risk and common mental health issues will benefit people with IBD and healthcare practitioners and will guide policy makers as allocation of resource may be guided by the real-world information produced by these studies. Trial registration number: NCT03836612 .